The effectiveness of combining rolling deformation with wire-arc additive manufacture on β-Grain refinement and texture modification in Ti-6Al-4V - Donoghue, Jack; Anthonysamy, Alphons Anandaraj; Martina, Filomeno; Colegrove, Paul A.; Williams, Stewart W.; Prangnell, Philip B. (Elsevier, 2016)
In Additive Manufacture (AM), with the widely used titanium alloy Ti–6Al–4V, the solidification conditions typically result in undesirable, coarse-columnar, primary β grain structures. This can result in a strong texture and mechanical anisotropy in AM components. Here, we have investigated the efficacy of a new approach to promote β grain refinement in Wire–Arc Additive Manufacture (WAAM) of large scale parts, which combines a rolling step sequentially with layer deposition. It has been found that when applied in-process, to each added layer, only a surprisingly low level of deformation is required to greatly reduce the β grain size. From EBSD analysis of the rolling strain distribution in each layer and reconstruction of the prior β grain structure, it has been demonstrated that the normally coarse centimetre scale columnar β grain structure could be refined down to < 100 μm. Moreover, in the process both the β and α phase textures were substantially weakened to close to random. It is postulated that the deformation step causes new β orientations to develop, through local heterogeneities in the deformation structure, which act as nuclei during the α → β transformation that occurs as each layer is re-heated by the subsequent deposition pass.
Keywords: Additive Manufacture; Titanium; Grain structure; Texture